MP26: Rate and outcome of incidental findings among abdominal computed tomography scans in the emergency department. (15th May 2017) - Bleeker, H.; Ohle, R.; Anjum, O.; Perry, J.J.
Abstract : Introduction: With the increased accessibility of computed tomography (CT), use in the emergency department has increased. Increased use has lead to a reduction in missed diagnoses but also an increase in radiation burden and the increased likelihood of incidental findings. In this study, we sought to characterize the use of abdominal CTs at an academic tertiary center in order to quantify the rate and clinical significance incidental findings.Methods: This was a retrospective chart review of radiological database of all abdominal CT ordered by the emergency department from January 1 st to March 21 st 2015. Incidental findings requiring follow up were defined by the American college of radiology guidelines. Clinically significant incidental findings were defined as those that resulted in a finding of malignancy or comparably serious disease. Abdominal CTs were excluded if they were ordered together with CT thorax. The data was abstracted by one trained reviewer using a standardized data collection sheet and 10% of the data was verified by a second reviewer. Inter-rater reliability reported by Kappa statistic. Data were reported as mean and standard deviation. A sample size of 770 was calculated based on an expected difference in prevalence between significant and non-significant incidental findings of 80% (α=5%, Power=90%).Results: A total of 1882 imaging studies were included (56.3% female, age 59.4 years (16.3), CTAS 3 (1.3). The most common presenting complaints: abdominal pain (980, 52.1%), flank pain (196, 10.4%) and nausea/vomiting (111, 6%). Indications included rule out (r/o) obstructing renal stones/colic (329; 17.5%), r/o diverticulitis/colitis (307; 16.4%) and abdominal pain not yet differentiated (283; 15.1%). The most common final diagnoses as a result of CT were renal stone/colic (212, 11.3%), colitis/diverticulitis (191, 10.2%), and bowel obstruction (111, 6%).Incidental findings recommending further imaging occurred in 93 (4.9%). Of these, 43 were completed, and 15 resulted in clinically significant findings: cancer of the colon (2), lung (2), bladder (2), metastatic cancer (2), adnexa (4), endometrium (1), lymphoma (1), and venous thrombus (1).Conclusion: Incidental findings are far less common (5%) then previously reported (as high as 30%) and rarely clinically significant.